Do Baseline Executive Functions Mediate Prospective Memory Performance under a Moderate Dose of Alcohol? - Smith-Spark, James H.; Moss, Antony C.; Dyer, Kyle R. (Frontiers in Psychology, 2016)
Prospective memory (PM) is memory for delayed intentions. While deleterious effects of acute doses of alcohol on PM have been documented previously using between-subjects comparisons, the current study adopted a single blind placebo-controlled within-subjects design to explore whether the extent to which alcohol-related impairments in PM are mediated by executive functions (EFs). To this end, 52 male social drinkers with no history of substance-related treatment were tested using two parallel versions of a clinical measure of PM (the Memory for Intentions Test; Raskin, Buckheit & Sherrod, 2010), and a battery of EF measures. Testing took place on two occasions, with the order of administration of the alcohol and placebo conditions being fully counterbalanced. Overall, PM was worse under alcohol and participants showed deficits on five of the six subscales making up the clinical test. Hierarchical multiple regression analyses demonstrated that EFs did not predict PM performance decrements overall but did predict performance when time cues were presented and when verbal responses were required. Phonemic fluency was the strongest of the EF predictors; a greater capacity to gain controlled access to information in long-term memory predicted a smaller difference between placebo- and alcohol-related performance on both the time cue and verbal response scales. Prospective memory is crucial to compliance with, and response to, both therapy programmes and alcohol harm prevention campaigns. The results indicate that individual differences in cognitive function need to be taken into account when designing such interventions in order to increase their effectiveness.